What is nature tourism? Case study: university students - Graja-Zwolińska, Sylwia; Spychała, Aleksandra (Turyzm/Tourism, 2013)
On the one hand in recent years nature tourism (turystyka przyrodnicza) has constituted a significant part of the tourism industry, on the other it has caused many problems for researchers attempting to define the phenomenon. Should the tourism destination or its primary motivation determine its categorisation? Is there indeed a need when considering practice as well as theory? The authors of the article have attempted a discourse with both foreign and domestic literature and subsequently sought to find the perceived meaning of turystyka przyrodnicza (nature tourism) amongst students of Poznań University particularly those associated with the natural environment on their degree courses. The present article should be considered as a contribution to further work in this field theoretically as well as practically.